(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The world’s most viewed sporting event is the FIFA World Cup. The historical evolution of football as a sport, its playing methods, and the possibilities and circumstances established for Uzbek football players are all covered in this article.